Histopathological changes in the gills of some fishes inhabiting polluted Singhiya river, Biratnagar, Nepal - Subba, Bharat Raj; Khanal, Bikash (Nepalese Journal of Biosciences, 2013)
Histopathological effects on the gills of a few fish species of polluted Singhiya river, Biratnagar sub-metropolis was made. The gills sections of Oxygaster bacaila, Neomacheilus botia,, Glossogobius giuris, Puntius sophore, Barillius barana, Channa gachua and Silorhynchus sucatio were found much deformed. Lesions, abnormal growth of taste buds and inter-lamellar space, fusion at the tips of primary as well as secondary lamellae, shifting of epithelial layer, deformation of gill head and that of outer margin, tilted secondary lamellae were found common. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7498 Nepalese Journal of Biosciences 2 : 113-117 (2012)